Kepemimpinan Perempuan dan Ketahanan Pangan: Upaya Bupati Irna Narulita dalam Penguatan Pangan Lokal di Pandeglang - Bayu Nurrohman; Yeby Ma'asan Mayrudin (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2021)
This study examines the efforts of woman local leader, namely Pandeglang Regent Irna Narulita in preparing food security in her region. This research is important because in the midst of the issue of gender mainstreaming and woman leadership, it is necessary to continue to work on it as a dedication to the central role of women. The researchers also wanted to analyze the leadership of woman local leader who are currently serving in building food strengthening. This research will provide another perspective in research because it will focus more on women's leadership in strengthening food, while other research on women's leadership sees more of women's representation. The locus of this research is in Pandeglang Regency, Banten Province, because seeing Pandeglang Regency is one of the areas led by woman. Furthermore, Pandeglang an area that still has a very wide potential of agricultural land in Banten. We use a qualitative method with a case study approach. The results of this research present the strengthening of food in Pandeglang Regency through the B2SA program and local food commodities (talas beneng and porang) that have been exported. Then the leadership of “Bupati” Irna was able to be more transformational than transactional. Because of its ability to encourage staff and stakeholders to work together to achieve common goals.